Educaring from the heart : how to nurture your wellbeing and rediscover your purpose in education - McGillicuddy, Deirdre (New York : Routledge, 2024)
"Inviting readers on a journey of self-reflection, Educaring from the Heart offers an approach to education which places care, empathy, and compassion at the core of the educator's role. Within the book, the reader is introduced to the principles underpinning educaring from the heart and encouraged to consider their own positionality when reflecting on the role they play in supporting both the learning and wellbeing of their students. Practical exercises are woven throughout to allow the reader to critically engage with how they understand themselves and their values as educators, and how this then shapes their wellbeing and practices in the classroom. The book is divided into three distinct sections: The "I" as Educator The "Us" as Educator and Student The "We" as Co-Creators for Wellbeing With a focus on nurturing wellbeing and learning within the classroom, as well as the power of co-creativity, this book is an essential read for any educator seeking to re/discover their purpose within education and to foster positive outcomes for their students"--
Educaring -- to the heart of the matter the "I" as educator -- The educator backpack -- Our values -- Our why -- Our wellbeing -- The "Us" as educator and student -- Nurturing the individual -- Compassionate education -- The power of the relational -- Empowering voice(s) -- The "We" as co-creators for wellbeing -- Co-creating heart-full education -- Creativity for wellbeing -- A framework for educaring from the heart.
Keywords: Reflective teaching; Teacher effectiveness; Effective teaching; Teacher-student relationships; EDUCATION / Professional Development